HUMAN RESOURCES COMPETENCE AND MANAGEMENT (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The development of a market economy has changed the requirements for the basic characteristics of staff, has increased the value of creative attitude to work and high professionalism of personnel. Thus, the issues of personnel management and its competence are considered as priority directions in improving the system of general management of the enterprise.It is substantiated that competence management is a set of measures performed at the enterprise aimed at identifying, acquiring, developing and maintaining those competencies of employees, which allow to achieve the strategic goals of the enterprise.Competence management is perceived as part of human resource management, which in turn is a part of business management. So, we can talk about enterprise management based on competencies when the set of competencies used in human resource management contributes to achieving the expected results of the enterprise. Human resources management is understood as a set of personnel-related activities aimed at achieving the goals of the enterprise and meeting the needs (development) of employees. The main goal of human resources management is to help the company gain competitive advantage through the success of its employees. As competencies are expected to provide an enterprise with a competitive advantage as a result of value added, it is justified to focus on a strategic approach in personnel management. Strategic human resource management is envisaged to include decisions and actions that address employees, which in the future guide staff activities to the success of the enterprise. The primary objective of strategic human resource management is to identify areas and ways to use human resources to achieve the goals of the enterprise.
Keywords: competencies, human resource management, strategic management, business management, competitive advantage